Knowledge, attitude, and practice of breast feeding mothers in a tertiary care centre: a descriptive study - Dr. Bindu A; Dr. Noushadali A K; Dr. Kutty.P M (Pediatric Review: International Journal of Pediatric Research, 2017)
Objective: Child feeding practices, including breastfeeding, affects the nutritional status of children under two years of age. Maternal knowledge and comfort of breastfeeding are factors that predict the feeding outcomes. The current study was designed to assess the knowledge, attitude, and practice regarding breastfeeding of mothers attending the outpatient department and Immunization clinic of a tertiary center in Kerala.Methods: This descriptive, cross-sectional study was conducted from August 2015 to October 2015. The study subjects included all eligible mothers with infants between 6 months to 1 year of age visiting the outpatient department and immunization clinic during the study period.Results: All participants had knowledge that child should be breastfed, but only 73% had knowledge about exclusive breastfeeding. In this study, more than half of the participants (62.5%) initiated breastfeeding within one hour of delivery. Only one-third of the participants practiced exclusive breastfeeding for more than 6 months.Conclusion: The present study shows that breastfeeding behavior among the study population is still far from optimal.